POSSIBLE ASSOCIATION OF VITAMIN D LEVEL IN PREGNANCY AND GESTATIONAL DIABETES - DR. BUSHRA J.AL-RUBAYAE (International Journal of Pharma and Bio Sciences, 2015)
Gestational diabetes affects maternal, foetal and neonatal outcome if detected early lessen complications on the mother and her foetus. The objective of the study is to find any association between maternal serum 25-dihydroxyvitamin D in the first, second trimester of pregnancy and development of gestational diabetes. Our study included one hundred sixty- six pregnant women, Serum levels of 25-hydroxyvitamin D were measured with an automated chemiluminescence immunoassay in the first trimester and second trimester with oral glucose tolerance test between 24-28 weeks of pregnancy for screening gestational diabetes. From one hundred sixty-six pregnant forty-five women had low vitamin D level in the first trimester and in the second trimester, from these thirty-two pregnant developed gestational diabetes which followed for the rest of pregnancy. Low level of vitamin D in pregnancy may be associated with development gestational diabetes.